Information Systems Foundations Part Three The Role of Design Science - Hart, Dennis (693fb54f-830b-41db-a34b-63e5004371d8, 2010)
This volume presents papers from the fourth biennial Information Systems Foundation Workshop, held at The Australian National University in Canberra from 2-3 October, 2008. The focus of the workshop was, as for the others in the series, the foundations of Information Systems as an academic discipline. The emphasis in this workshop was on the movement known as 'Design Science' and its importance in practical disciplines such as Information Systems. The chapters in the volume provide a critical examination of current design science ideas, with the role of human creativity given special mention. The philosophical underpinnings of design science thinking are also examined. Practically, the volume shows how the design science approach can be used in academic research that leads to artefacts that add value for individuals, organizations and society.